The Information Provision in the Corporate Acquisition Process: Why Target Firms Obtain Multiple Fairness Opinions - Liu, Tingting (The Accounting Review, 2020)
ABSTRACT Using a hand-collected dataset for takeovers from 1996 to 2013, I examine why some target firms obtain a second fairness opinion and the associated wealth effects of doing so. I find that multiple opinions are more likely to be used in deals in which management/investment bank conflicts of interest are high—e.g., buyouts and stapled financing deals. In addition, the use of a second opinion has a significantly positive impact on target shareholders' wealth in these two types of deals. Fairness opinion valuation predominantly relies on accounting data, and the benefit of seeking a second opinion increases with a firm's earnings quality. Collectively, the results suggest that a second opinion is used to facilitate transactions. JEL Classifications: G34; G24; J33.